2021
DOI: 10.1007/s10064-021-02490-1
|View full text |Cite
|
Sign up to set email alerts
|

Development characteristics and dynamic mechanisms of tectonic ground fissures in Weihe Basin, China

Abstract: The Weihe Basin is part of the regionally extensive Fenwei Graben System, which is a major tectonic block impacted by active tectonics and human activities. There are 200 tectonic ground fissures in the Weihe Basin, some of which have resulted in loss of life and severe damage to infrastructure. The development characteristics and dynamic mechanisms of these fissures were investigated by surveying, mapping, and geological drilling. The fissures are distributed along the boundary faults between fault blocks wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 46 publications
0
5
0
Order By: Relevance
“…In China, nearly 100 cities, including those in the Yangtze River Delta [8][9][10], North China Plain [11,12], Fenwei Basin [13,14], and Pearl River Delta, are affected by land subsidence disasters [15,16], covering a total land subsidence area exceeding 79,000 km 2 [17]. Statistical analysis by Mehdi Bagheri-Gavkosh revealed that the eastern part of China's Yangtze River Delta registers among the regions with the highest average land subsidence values [18].…”
Section: Introductionmentioning
confidence: 99%
“…In China, nearly 100 cities, including those in the Yangtze River Delta [8][9][10], North China Plain [11,12], Fenwei Basin [13,14], and Pearl River Delta, are affected by land subsidence disasters [15,16], covering a total land subsidence area exceeding 79,000 km 2 [17]. Statistical analysis by Mehdi Bagheri-Gavkosh revealed that the eastern part of China's Yangtze River Delta registers among the regions with the highest average land subsidence values [18].…”
Section: Introductionmentioning
confidence: 99%
“…Tectonic fissures are a geological hazard resulting from tectonic forces and are typically closely associated with fault activity [11]. Numerous publications from diverse countries and regions have addressed and investigated tectonic fissures that are controlled by faults [2,[11][12][13][14][15][16]. Tectonic fissures are often linked to endogenic geological processes, with crustal extension and differential block movement being crucial factors in their formation [13,16].…”
Section: Introductionmentioning
confidence: 99%
“…Numerous publications from diverse countries and regions have addressed and investigated tectonic fissures that are controlled by faults [2,[11][12][13][14][15][16]. Tectonic fissures are often linked to endogenic geological processes, with crustal extension and differential block movement being crucial factors in their formation [13,16]. This phenomenon is commonly observed in areas with high tectonic activity, such as rifts and basins.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although a lot of research has been conducted on ground fissures all over the world, the main focus has been on the development characteristics of ground fissures, the shear model of soil, causal mechanisms, and the influence of ground fissure activities on underground engineering structures [20][21][22][23][24][25][26][27]. Yan et al [28] focused on the failure mechanism and deformation characteristics of a utility tunnel based on the Kunming Road utility tunnel crossing f3 ground fissure by finite-difference numerical simulation.…”
Section: Introductionmentioning
confidence: 99%